'A world without man-made pollution' - lessons learnt from COVID-19 and sustaining the pollution decline for the sake of future generations - S. M. Arnold; Pasyodun Koralage Buddhika Mahesh; Sameera Senanayake; Dimuth Peiris; Withanage Iresha udayanagani Jayawickrama; Sathira Perera; Thilanka Bandara; Nalin Ariyaratne; Naveen Soysa; Samantha Ananda; Inoka Suraweera (College of Community Physicians of Sri Lanka, 2020)
No abstract available